Induction of hair follicles using neonatal mouse dermis and human keratinocytes: relevance for improved burn wound treatments - Malise, Thudzelani Takalani Austin (Division of Cell Biology, 2020)
Second degree burns result in the destruction of the skin as well as its adnexa. Following such burns the wound heals without the formation of skin appendages and hair follicles. In normal embryonic development hair follicle formation requires the interaction between epithelial (keratinocytes) and mesenchyme cells. Attempts to recapitulate the process of hair induction in wounded skin in vitrousing human cells have to date been unsuccessful. The aim of this project is to attempt to elicit the early steps of hair follicle formation (induction) by co-culturing primary human keratinocytes with embryonic murine mesenchyme cells and assessing changes in expression patterns of genes associated with or reflective of induction. Mesenchymal cells and keratinocytes cells were obtained by enzymatically digesting dorsal neonatal mouse skin and neonatal human foreskin using dispase and collagenase. Cells were cultured separately, and their growth dynamics measured. The isolated neonatal mouse mesenchymal cells were shown to have hair induction potential because they expressed dermal papilla signature genes, Alp, Sox2 and Vcan. However, this characteristic was lost during in vitro propagation suggesting that mesenchymal cells lose their hair inductive potential during culture. In contrast, when cultured at high densities or in spheroids in hanging drops, the dermal papilla signature genes were upregulated suggesting that this might be a way to maintain inductive potential. Primary foreskin keratinocytes expressed high levels of basal layer marker, keratin 5 (K5), and low levels of the early differentiation marker, K10, suggesting that the isolated keratinocytes have stem cell properties. When co-cultured with neonatal mouse mesenchymal cells using Transwells, the mesenchymal cells were able to elicit colony formation on keratinocytes in co-cultures, indicating that they support keratinocyte proliferation. It was not possible to do hair follicle induction marker analysis of human foreskin keratinocytes cocultures because of challenges and difficulties encountered during expansion. Therefore, Immortalised HaCaT keratinocytes were tested. HaCaT keratinocytes were shown to be induced during cocultures because they upregulated Wnt signalling genes, β-catenin and NF-KB. As an additional approach, human foreskin keratinocytes were cultured in medium containing Wnt signalling pathway ligand, Wnt3a. β-catenin and NF-KB were slightly reduced, and only Lef1 was upregulated in human foreskin keratinocytes cultured in Wnt3a conditioned medium. The results of this study show that neonatal mouse mesenchymal cells have hair inducing capabilities and it is lost by in vitro propagation and can be restored by spheroid cell culture. The results also demonstrate that human foreskin keratinocytes need to be expanded using efficient culture methods to maintain an undifferentiated state.